2007
DOI: 10.3748/wjg.v13.i14.2066
|View full text |Cite
|
Sign up to set email alerts
|

Surgical anatomy of innervation of the gallbladder in humans andSuncus murinuswith special reference to morphological understanding of gallstone formation after gastrectomy

Abstract: The route from the anterior hepatic plexus via the cystic artery and/or duct is crucial for preserving gallbladder innervation. Lymph node dissection specifically in the hepatoduodenal ligament may affect the incidence of gallstones after gastrectomy. Furthermore, the route from the posterior hepatic plexus via the common bile duct and the cystic duct to the gallbladder should not be disregarded. Preservation of the plexus may attenuate the incidence of gallstone formation after gastrectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 34 publications
2
55
1
Order By: Relevance
“…Damage of the nerve fiber that innervated the gallbladder in the hepatoduodenal ligament may be the underlying mechanism for this phenomenon [6]. However, the extent and detail of lymph node dissection done for the patients were not available in our database.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Damage of the nerve fiber that innervated the gallbladder in the hepatoduodenal ligament may be the underlying mechanism for this phenomenon [6]. However, the extent and detail of lymph node dissection done for the patients were not available in our database.…”
Section: Discussionmentioning
confidence: 99%
“…The reported incident rate was usually around 10-25%, but rates as high as 47 and 60% had been cited in previous studies [3][4][5]. Possible mechanisms associated with this increased incidence included vagotomy, extent of gastrectomy, method of gastrointestinal reconstruction, and lymph node dissection [6,7]. Some authors advocated prophylactic cholecystectomy, simultaneous removal of the gallbladder during gastric resection to prevent potential gallstone-related sequelae, such as cholecystitis, cholangitis, and pancreatitis [8].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies reported a three-four fold increased incidence 5 years after gastric surgery (up to 15-25 %) [1][2][3][4][5][6] with an estimated mean value of 17 % in all studies [1][2][3][4][5][6][7]. The underlying mechanism was thought to be related to surgical dissection of the vagus nerve branches and the anatomical gastrointestinal reconstruction [5,[8][9][10], and to the extent of gastrectomy and lymphadenectomy [1,4,[11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…7,8,10 In our patient, however, Pheochromocytoma Manifesting Persistent Right Shoulder Pain and Hypochondralgia Right shoulder pain associated with liver diseases is well known as a representative referred pain. 15 The adrenal gland is located at retroperitoneal space and any pathological changes usually do not influence the phrenic nerve. 14 Similarly, the right shoulder pain in our case was assumed to occur as a referred pain derived from the adrenal tumor.…”
Section: Discussionmentioning
confidence: 99%